Spatial continuity and stress transfer: Primary and complementary factors shaping pure-swarm laboratory catalog into mixed burst-like and swarm-like - Qiquan Xiong; Qing Lin; Yue Gao; Jesse C. Hampton (Journal of Rock Mechanics and Geotechnical Engineering)
Natural earthquakes and micro-seismicity resulting from hydraulic fracturing or other engineering practices display distinctively different spatial-temporal features, like mixed burst- and swarm-like features or predominantly swarm-like features. The mechanism(s) contributing to such observations can be diverse. We present the inspections on the dynamic formation process of the single swarm-like tree in laboratory acoustic emission (AE) catalogs. Such largest swarm-like trees can contain >97% AE events from the entire catalog within a test; and all catalogs under investigation display scale-invariance features. The formation of the largest swarm-like tree correlates with the rock fracture process analogue of the source pervasive process, where its AE releases exhibit significant spatial well-organization. Comparison to other laboratory catalogs under different laboratory settings helps us identify the spatial continuity of the rock fracture process as the primary factor in forming the largest swarm-like trees at laboratory scale. The stress transfer process is involved in the rock fracture process for the tests having pre-existing spatial discontinuity. Artificial perturbations on the spatial information induced by the stress transfer process further confirm that stress transfer also serves to shift the pure swarm-like catalog into a mixed burst- and swarm-like catalog. These laboratory observations may provide inspirational insights for understanding the field-scale mechanism(s) shaping the spatial-temporal energy release features.